Patient satisfaction with nursing care in surgical departments - Jarosova, Darja; Janikova, Eva; Vrublova, Yvetta; Zelenikova, Renata; Tomaskova, Hana; Papastavrou, Evridiki (My University, 2011)
Aim: The aim of the study was to assess patients' satisfaction with the nursing care provided in surgical departments, to determine relationships between demographic and clinical characteristics of patients and their satisfaction, and to compare patients' satisfaction according to the medical facilities where they were hospitalized. Methods: A descriptive correlation study. The research sample consisted of 279 patients from the surgical departments of four hospitals in Ostrava and its surroundings. Data were collected in the autumn of 2009 using the standardized instrument Patient Satisfaction Scale (PSS). Results: Patients rated the items, which are grouped into three factors: -technical/rational, - information, - interaction and support on the four-point Likert scale. In all of the hospitals, the patients were most satisfied with the technical aspects of the nursing care, but less satisfied with the information provided to them. Patients valued the professionalism of nurses the most. Only two demographic characteristics influenced patients' satisfaction: - education, and - length of hospitalization. Patients with higher professional education were more satisfied than patients with secondary education. Patients hospitalized for more than a week expressed greater satisfaction in all assessed areas of the questionnaire. There were no significant differences in the evaluation of patients' satisfaction among the hospitals. Conclusion: The results of the study did not demonstrate any statistical differences in patients' satisfaction according to hospital, nor were there demonstrated any significant effects of demographic factors on their satisfaction. The Patient Satisfaction Scale is an example of a quality instrument with proven psychometric parameters, which is suitable for measuring patient satisfaction with nursing care in the Czech environment.
Keywords: Nursing care; Patients; PSS instrument; Satisfaction